Indole Alkaloids of Rauvolfia ligustrina and Their Anxiolytic Effects in Adult Zebrafish - de Sousa, Herbert Magalhães; da Silva, Alison Batista; Ferreira, Maria Kueirislene Amâncio; da Silva, Antonio Wlisses; de Menezes, Jane Eire Silva Alencar; Marinho, Emmanuel Silva; Marinho, Márcia Machado; dos Santos, Helcio Silva; Pessoa, Otilia Deusdênia Loiola (Planta Medica, 2023)
Rauvolfia species are well known as producers of bioactive monoterpene indole alkaloids, which exhibit a broad spectrum of biological activities. A new vobasine-sarpagan-type bisindole alkaloid (1) along with six known monomeric indoles (2, 3/4, 5, and 6/7) were isolated from the ethanol extract of the roots of Rauvolfia ligustrina. The structure of the new compound was elucidated by interpretation of their spectroscopic data (1D and 2D NMR and HRESIMS) and comparison with published data for analog compounds. The cytotoxicity of the isolated compounds was screened in a zebrafish (Danio rerio) model. The possible GABAergic (diazepam as the positive control) and serotoninergic (fluoxetine as the positive control) mechanisms of action in adult zebrafish were also evaluated. No compounds were cytotoxic. Compound 2 and the epimers 3/4 and 6/7 showed a mechanism action by GABAA, while compound 1 showed a mechanism action by a serotonin receptor (anxiolytic activity). Molecular docking studies showed that compounds 2 and 5 have a greater affinity by the GABAA receptor when compared with diazepam, whereas 1 showed the best affinity for the 5HT2AR channel when compared to risperidone.
Keywords: Rauvolfia ligustrina; Apocynaceae; alkaloids; zebrafish; Danio rerio; anxiolytic effect